ANALISIS INTERAKTIF PEMANFAATAN SISTEM INFORMASI AKADEMIK PADA PERGURUAN TINGGI DI KOTA BATAM - Dwi Suminarno (Computer Based Information System Journal, 2013)
This study aims to provide recommendations for designing information systems academic at several universities in Batam by using the concept of Human Computer Interaction. The method used is a qualitative method using inductive analysis approach to the exclusion of the initial hypothesis of the study, still looking for patterns, shapes and themes to express the data systematically. The results of this research is the concept of Human Computer Interaction applied to the SIA on two campuses in Batam is still not implemented, due to usability, system functionals, effective and efficient yet been fully implemented. Recommendation that the writers are designing a Web-based AIS (Web based), with due regard to the basic concepts of HCI.